2023
DOI: 10.1038/s41598-023-32985-8
|View full text |Cite
|
Sign up to set email alerts
|

The phase of plasticity-induced neurochemical changes of high-frequency repetitive transcranial magnetic stimulation are different from visual perceptual learning

Abstract: Numerous studies have found that repetitive transcranial magnetic stimulation (rTMS) modulates plasticity. rTMS has often been used to change neural networks underlying learning, often under the assumption that the mechanism of rTMS-induced plasticity should be highly similar to that associated with learning. The presence of visual perceptual learning (VPL) reveals the plasticity of early visual systems, which is formed through multiple phases. Hence, we tested how high-frequency (HF) rTMS and VPL modulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…In a recent study utilizing MRS glutamate and GABA concentrations were measured to obtain insight into possible differences of visual perceptual training-induced learning and perceptual changes induced by high-frequency rTMS application. It was found that the time courses of the changes of GABA and glutamate differed as well as the contribution of both transmitters suggesting different underlying mechanisms, although both approaches involve changes in excitation and inhibition ( Lin et al, 2023 ).…”
Section: Other Markers Of Excitation-inhibitionmentioning
confidence: 99%
“…In a recent study utilizing MRS glutamate and GABA concentrations were measured to obtain insight into possible differences of visual perceptual training-induced learning and perceptual changes induced by high-frequency rTMS application. It was found that the time courses of the changes of GABA and glutamate differed as well as the contribution of both transmitters suggesting different underlying mechanisms, although both approaches involve changes in excitation and inhibition ( Lin et al, 2023 ).…”
Section: Other Markers Of Excitation-inhibitionmentioning
confidence: 99%
“…Typical induction protocols for LTD are around 1 Hz, with 900 pulses at 1 Hz being common in the literature (248). However, recent r-TMS studies have shown that a 10Hz frequency can induce plasticity (249). Parallel to this, our lab has recently shown that an induction protocol of 6000 pulses at 10 Hz induces an isoform of LTD that is endocannabinoid dependent (6).…”
Section: Introductionmentioning
confidence: 99%